2013
DOI: 10.5897/ajb2013.12446
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal DNA variation in landraces of bambara groundnut

Abstract: The ribosomal DNA (rDNA) is a basic component of all eukaryotic chromosomes which codes for rRNA. The rDNA is made of tandemly repeated units of 18S, 5.8S, 28S, ITS and IGS. The 18S, 5.8S and 28S are coding regions while the ITS and IGS are non coding. The rDNA evolves in a concerted manner such that rDNA units within an individual are almost completely identical making it a useful tool in taxonomic studies. The rDNA marker is used to discriminate between species in the same or different genus. Bambara groundn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Gene flow among the growth types varied from 11.48 (between bunching and semi-bunching types) to 12.92 (between bunching and spreading). These results agree with the report of Waziri et al(2013). Ketema et al(2020) suggested that gene flow > 1 is adequate to neutralise the genetic differentiation between two populations.…”
Section: Discussionsupporting
confidence: 92%
“…Gene flow among the growth types varied from 11.48 (between bunching and semi-bunching types) to 12.92 (between bunching and spreading). These results agree with the report of Waziri et al(2013). Ketema et al(2020) suggested that gene flow > 1 is adequate to neutralise the genetic differentiation between two populations.…”
Section: Discussionsupporting
confidence: 92%
“…According to FAO [54], nearly 6145 Bambara germplasms are held in ex situ conservation around the world, with collections from the national and international gene banks (Table 3). Waziri et al [88] reported that the Genetic Resource Center (GRC) under IITA, Nigeria, has 2031 accessions accumulated from several sub-Saharan African countries. Traditional or rural growers of Bambara groundnut farmers depend on the existing diversity among the germplasm, which they cultivate, and ecological selection on Bambara groundnut germplasms has helped to maintain genetic diversity [78].…”
Section: Characterization and Conservation Of Genetic Resourcesmentioning
confidence: 99%
“…Previous research has shown that a significant agro-morphological variation exists among many local genotypes of Bambara groundnut [56]. Bambara groundnut demonstrates a considerable amount of genotypic variability for various phenotypic, physiological, agronomic and seed traits [55]. Studies focused on variation in inter and intra-landrace morphological descriptors (both as sovereign research and as an extensive classification of germplasm) in Bambara groundnut has been comprehensively reported [34,73,74].…”
Section: Genetic Diversity In Bambara Groundnutmentioning
confidence: 99%
“…WT: wild types; LR: landraces; BL: breeding lines; AC: advanced cultivars; OT: others. Source:[54,55]. International Institute of Tropical Agriculture (IITA).…”
mentioning
confidence: 99%